Analysis of Marketing Margins and Farmers’ Shares on Corn in Sigi Regency, Central Sulawesi, Indonesia - Heni Sulistyawati Purwaning Rahayu; Mardiana Dewi; Muhammad Abid (Universitas Sebelas Maret, 2021)
An increase in corn productivity is not always followed by an increase in farmer income and welfare. The sustainability of farms must be supported by its economic viability including the marketing aspect. This study aimed to analyze the marketing of corn in Sigi Regency, Central Sulawesi Province. This research applied qualitative and quantitative methods. Marketing channel and marketing margin were analyzed descriptively, while farmer share was analyzed quantitatively using variance analysis (ANOVA). The results have shown three types of corn marketing channels, namely: 1) channel I, consisting of farmers-consumers, 2) channel II, covering farmers-collectors, traders-retailers and traders-consumers and 3) channel III, including farmers-collectors and traders- feed industries. Channel II has the highest marketing margin, followed by channel III and I, respectively. The intermediaries determine marketing costs that affect marketing margin and farmers’ shares. Channel I has the highest farmers’ shares, followed by channel III and channel II, respectively. The results of the significant difference test have revealed a difference in farmers’ shares in the marketing channels; and hence, the choice of marketing channel significantly determines the farmers’ shares. Therefore, farmers should shorten the marketing chain and strengthen their bargaining position by activating groups. Meanwhile, the government can play an active role so that farmers can have an access to strengthening capital and marketing.